The Role of Sharia Supervisory Board Diversity on The Transparency of Islamic Social Reporting - Chindy Aidil Fitri Rukmana; Ine Mayasari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Along with the rapid development of Islamic banks in Indonesia, corporate responsibility has become greater towards social life. The purpose of this study is to examine the role of the characteristics of the Sharia Supervisory Board (SSB) in increasing the disclosure of social responsibility of Islamic banking in Indonesia using the Islamic Social Reporting (ISR) index for the period 2015-2022. The SSB characteristics tested in this study are size, frequency of meetings, dual positions, expertise, age, and proportion of women. This study uses a quantitative method with a sample of the entire population of this study, namely all Indonesian Islamic Commercial Banks (ICB) registered with the OJK during the 2015-2022 period, namely 16 ICB. This research was then tested using the STATA 17 application with panel data regression analysis. Based on the research results, the selected model estimate is the Fixed Effect Model (FEM). This study also uses a robustness test so that the results show valid data and are free from heteroscedasticity symptoms. The results of hypothesis testing show that simultaneously all SSB characteristics in this study have a significant effect on ISR disclosure. Meanwhile, partially, the size, dual positions, and proportion of women in SSB have a significant effect on ISR disclosure with SSB size having a negative direction of influence. While the frequency of meetings, expertise, and age of SSB have no partial influence on ISR disclosure. This study contributes to BUS in Indonesia and DSN-MUI in terms of decision making regarding the characteristics of SSB that are appropriate for the placement of SSB in Indonesian Islamic banks and can enrich the literature on Good Corporate Governance (GCG) and Islamic Social Reporting (ISR).